A trajectory optimization method for improved tracking of motion commands using CNC machines that experience unwanted vibration - Okwudire, C.; Ramani, K.; Duan, M. (CIRP annals, 2016)
This paper presents a trajectory optimization method for minimizing tracking errors in CNC machines that experience unwanted vibration. The motion command sent to the machine is parameterized using B-splines whose basis functions are filtered using a model of the machine's dynamics. The control points associated with the filtered basis functions are then selected to minimize tracking errors subject to the kinematic limits of the machine. The proposed method is shown to be very systematic and easy to use, and it does not sacrifice tracking speed. Experiments are used to demonstrate its superior performance compared to an existing method.